Status and distribution of foliar diseases of poplar in Himachal Pradesh - SANJEEV SHARMA, R.C. SHARMA and (Indian Phytopathology, 2002)
A survey on the status and distribution of foliar diseases of poplar (Populus ciliata, P. deltoides, P. yunnanensis, P. eugenii [P. canadensis] and P. alba) was conducted during 1997-98 in the poplar growing areas under different agro-climatic zonesof Himachal Pradesh, India. Seven fungal diseases were recorded during the survey. Poplar rust, caused by Melampsora ciliata, was prevalent in all the agro-climatic zones. Cladosporium leaf spot (C. humile) was recorded in certain pockets of Solan (zoneII), Kullu (zone III), Lahaul Spiti and Kinnaur (zone IV) districts. Powdery mildew, caused by Uncinula salicis, was recorded at higher altitudes while Septoria (S. populi), Sphaceloma (Sphaceloma populi) and Alternaria (A. alternata) leaf spots occurred only at lower altitudes. Taphrina leaf blister (T. aurea) of poplar was recorded from one location only. The severity of various diseases in the different zones are discussed.